Application of GIS technology in cross-border tourism cooperation planning - Han, F.; Aday, A.; Zhandilla, B.D. (BUKETOV BUSINESS REVIEW, 2023)
Object: The emphasis in this paper is put on the use and importance of GIS technology in tourism. This paper takes the spatial pattern of cross-border tourism cooperation in the Altai Mountains region as the research object. Methods: The research methods are: the terrain analysis, three-dimensional scene simulation, data statistics, suitability analysis, visual domain analysis, transportation network analysis, and project site selection of GIS technology in tourism planning. Findings: The presented research is analytical in nature. The specific application of GIS technology in tourism planning is discussed. Also, 7 types of GIS applications were considered in the paper. In summary, GIS is mainly composed of data input system, data management system, spatial analysis system and data output system. Conclusions: The results of a study of the landscape features of Altai Mountains using GIS technologies prove that the tourist capabilities of the region provide an excellent opportunity to create an international cross-border tourist point. In addition, the full use of GIS technologies in tourism planning can significantly increase the scientific, urgency and efficiency of planning. This is one of the most important directions for the future development of tourist planning.